Numerical modeling of wave-induced liquefaction around a gravity-based structure - Kirca, V. S. Ozgur; Angin, Mert; Sumer, B. Mutlu (Frontiers in Built Environment, 2025)
Residual liquefaction, a significant issue in marine engineering, results from accumulated pore-water pressure in the seabed due to cyclic shear stresses, which compromises soil stability. This study aims to investigate residual liquefaction around gravity-based marine structures by means of a 2D numerical model. The model employs a two-step procedure: First, the stresses in the soil domain are determined via solving Biot equations, and subsequently the generation and diffusion of accumulated pore pressure in the soil is simulated by means of a pressure diffusion equation with a source term. The model was first validated against analytical solution for pore pressure buildup in the seabed under progressive waves, and against experimental data for residual liquefaction around a buried submarine pipeline. The results showed that the model can satisfactorily capture pore pressure buildup and residual liquefaction in the seabed around structures. Once validated, the model was utilized to model the pore-water pressure buildup and residual liquefaction potential around a caisson breakwater under the action of standing waves and the wave-induced rocking motion of the caisson, separately and in combination. Spatial distribution of liquefaction potential was determined in the seabed soil around the caisson with and without a bedding layer on the seabed. The model results revealed the critical role of the bedding layer in reducing liquefaction susceptibility under standing waves and rocking motion, and highlighted that the rocking motion alone poses a significant risk of inducing residual liquefaction in the seabed around the caisson.